A novel ultra performance liquid chromatography-PDA method development and validation for darunavir in bulk and its application to marketed dosage form - Sabyasachi Biswal; Sumanta Mondal; Prasenjit Mondal (Wolters Kluwer Medknow Publications, 2021)
Aims and Objective: The aim of this study was to develop and validate a novel ultra-performance liquid chromatographic method for estimation of darunavir in a bulk and tablet dosage form. Materials and Methods: The chromatographic separation was achieved using DIKMA Endoversil (2.1 mm x 50 mm, 1.7 µm) column. A mixture of 40% buffer (0.1% octa sulfonic acid) and 60% acetonitrile was used as a mobile phase with the isocratic elution mode and eluent was monitored at 281nm using UV detector. The method was continued and validated in accordance with International Conference on Harmonization Guidelines. Validation study revealed the specificity and reliability of the method. Results: In this method, darunavir was eluted with retention time of 0.516 min. Calibration curve plots were found linear over the concentration ranges 10-50 μg/mL for darunavir. Limit of detection was 0.02 μg/mL and limit of quantification was found 0.07 μg/mL. The present method was also found stable in force degradation study. Conclusion: The empirical evidences of all the study results revealed the suitability of the estimation of darunavir in bulk and tablet dosage form without any interference from the excipients.